Detection of Bactrocera oleae (Diptera: Tephritidae) DNA in the gut of the soil species Pseudoophonus rufipes (coleoptera: Carabidae) - Albertini, Alice (2018)
Pest control service provided by natural enemies of Bactrocera oleae, the key pest of the olive tree, is nowadays recognized as fundamental. B. oleae has developed resistance to common insecticides, and negative effects both on consumers’ health and non-target species are the major drawbacks of conventional control strategies. Carabid beetles are potential B. oleae pupae predators, but their predation on field still need to be assessed. We tested adult Pseudoophonus rufipes, a species known to be active in olive orchard when pest pupae are abundant in the soil, in order to detect B. oleae pupae consumption at different post feeding times for both male and female carabids. An already existing protocol was used for detecting B. oleae mtDNA sequences of the cytochrome oxidase subunit I gene in carabids’ gut, and its versatility improved. B. oleae mtDNA was detected up to 20 h after pupa ingestion with a high percentage of success, without significant differences between sexes and pair primers used. Prey DNA extraction was tested from both dissected and non-dissected carabids, obtaining comparable results. The trapping system used to collect carabids for molecular assays and the new elements introduced in the protocol represent cost-effective solutions that may be beneficial for future laboratory trials and, mostly, for the analysis of field-collected predators. Fostering the investigation of soil predators in olive orchard may increase the design of conservation control strategies against B. oleae.